A review on fibres and fillers on improving the mechanical behaviour of fibre reinforced polymer composites. (2021) - Sharma, Manoj; Sharma, Rajeev; Chandra Sharma, Shashi
Abstract: In the last few decades, researchers are continuously working on fiber composite materials for replacing conventional materials in various applications such as automotive, medical, agricultural, thermal management area and building insulation. Natural fibers like coir, sisal, hemp, jute, date palm, sugarcane bagasse and fillers like coconut shells, groundnut shells and rice husks, etc. are easily available in India. These fibers can be used successfully for improving the various mechanical and thermal properties when mixed with polymer materials (both thermoplastic and thermosetting) in proper proportion. It will also be helpful to reduce natural waste in the environment as well as provide the composite material at a lower cost. This review paper focused on the enhancement of mechanical, thermal, and tribological properties of fiber-reinforced polymer composite with or without filler. Since a composite material is composed of at least two materials, which combines to give properties superior to those of the individual constituents so it is important to select correct fiber and resin combination in accordance with the application. Some filler such as graphite, minerals and talk are added to improve the properties of a polymer composite, like graphite improves the lubrication property. Some fiber needs surface modifications and moisture removal before processing hence some important factors which affect the properties of fiber composites like fiber orientation, surface treatments, fiber size, and methods of production are also highlighted. It is observed from literatures that different modelling methods are effectively evolved and these methods help to design the fiber composite materials with close outcomes alongside experimentations approach. This paper discusses the importance of fibers and fillers aiming to improve the mechanical behaviour of fiber reinforced polymer composites with reference to the literatures already published. The points focused on for reviewing the literatures are their outcomes, factors influencing fiber selection, and applications.